Évaluer les bénéfices de la protection d’une zone humide : application aux sites du Conservatoire du littoral du Bassin d’Arcachon - Thomas Binet; Isabelle Mercier-Delacourte; Ambre Diazabakana; Nastasia Keurmeur (VertigO)
This article presents the results of an economic valuation of the benefits of the Conservatoire du Littoral’s land acquisition strategy in the Arcachon Bay (France). The developed approach is built on the classical methods of economic valuation of ecosystems and compares impacts of two prospective scenarios regarding ecosystem services provision toward 2050: i) a “strong protection” scenario relating to the full implementation of the long-term acquisition strategy of the Conservatoire du Littoral; and ii) a “weakening protection” scenario where this strategy is not implemented. Both scenarios integrate the ability of ecosystems to adapt in modeling variation of ecosystem services provision impacted by two major factors: first, threats to ecosystem for which it is possible to apply models built from past trends; then, management measures related to the Conservatoire’s acquisition and management strategy that may generate ruptures. The ecosystem valuation heavily relies on mapping tools to spatialize habitats, ecological and hydrological connectivities and consequently ecosystem services flows. The comparison of ecosystem services values calculated for each of the two scenarios estimates the benefits of Conservatoire du Littoral’s protection within the Arcahon Bay around 73.4 million euros over the period 2015-2050, with an average 2.1 million euros per year. This method provides sound insights as an advocacy tool to promote ecosystem conservation. The comparison of prospective scenarios of biodiversity, method still undervalued by policy makers, allows to develop relevant economic results to guide decision. These results enable to assess potential benefits of future choice and not to justify the past ones. Surely, this method suffers from a lack of data and the assertion of several hypotheses, but it is a powerful tool to design and promote a sustainable management of ecosystems, based on the maintenance of ecological functioning and the provision of ecosystem services and as part of a broader land planning and management approach that uses mapping and socioeconomic modelling.